Potensi Dan Peluang Kawasan Perdesaan Sebagai Daya Tarik Wisata ( Studi Kasus di Pedusunan Tunggularum, Wonokerto, Turi Sleman) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT: Rural area in the slope of Mount Merapi, Sleman Regency Dl Yogyakarta Province, has potential attraction to be developed as a tourist destination, especially rural tourism. Environment component in which includes physic, biologist, and socio cultural are integrated. In other side Tunggularum, Wonokerto Turi Sleman regency have natural resources that can be developed as rural tourism. Salak Pondoh (Sallaca edulis cv Pondoh) agricultural and local art-cultural activities in these area contribute value added for these area as an alternative tourism. The objectives of this study are to discover the potential and opportunities to developing rural tourism at Tunggularum and to absorb the perceptions of the local community with tourism activities. Collecting data has been done by using the method of survey and in-depth interview, basic research to know the distribution of a potential object and the local community perceptions